La aristocracia de Castilla y sus abogados celestiales (Estudios de Historia de España, 2016)
This article studies the relationship between the aristocracy of Castile and the saints as protectors in life and in the time of death. From his last wills and the recommendations contained in the treaties of the genus Ars moriendi, points out the differences between the links they have with the celestial world power elites, and the rest of society. Also, discusses the reasons to choose certain Saints as advocates. These are based on the primacy given to Christ environment, the request for assistance to the blessed that help to those who will leave this world to the salvation of the soul, and also to the titular group defenders and the titular saints of churches and monasteries under he lord’s patronage.
Keywords: Nobility; Piety; Saints; Lawyers; Death; Late Middle Ages